Formation of competencies in the process of teaching disciplines of the elective courses of the educational program in 33.05.01 “Pharmacy” training program - Irina Nikolaevna Dyakova (Вестник Майкопского государственного технологического университета)
The relevance of the research topic consists in assessing and comparing the formation of competencies in future pharmacists in two educational standards (FSES HE 3+ and FSES HE 3 ++). The purpose of the research is to study the formation and implementation of competencies in the professional field on the example of some disciplines of the elective courses of the educational program in the field of Pharmacy according to the Federal State Educational Standard 3+; to consider the formation of competencies of the Federal State Educational Standards of Higher Education 3 ++. The following research methods were used: analysis of literary sources, synthesis, comparison method. As a result of the study, it was determined that the elective disciplines of the Federal State Educational Standard of Higher Education 3+ mastered most of the professional ones, one third of the general professional ones and half of the general cultural competencies in addition to the basic disciplines. The competency-based approach in educational activities in the field of Pharmacy continues to develop and undergo significant changes, which are reflected in the new Federal State Educational Standard 3+. According to the new standard, the organization forms professional competencies independently on the basis of professional standards and the needs of the regional labor market, thereby striving to bring educational disciplines closer to the primary accreditation of a specialist and to the professional activities of a pharmacist.